The Role of Financing Products in Sharia Banks in Developing Halal Industry for Public Welfare - Siti Nurhasanah; Suryani Suryani; Ratu Humaemah (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
This article aims at exploring the role played by sharia banks’ financing products in developing the halal industry in Indonesia. The method used is qualitative descriptive with a study of literature. Based on the analysis result, it can be concluded that the role played by sharia banks is not limited only to providing financing products; instead, they also give some contributions to the development of the halal industry. The financing provided to people, particularly MSME actors, is allocated for halal industries, which keep on developing as halal has been a lifestyle for Indonesian Muslims. In response, the accessibility to products, service quality, and infrastructures in sharia financial industries are increased. The sharia banks’ financing products can play a significant role in national development and public welfare.